Financial Management Accountability of Mosque in Covid-19 Pandemic: The Religious and Humanist Side Exploration - Fitria, Yunita; Diyanti, Ferry; Bone, Hariman (Jurnal Ilmiah Akuntansi dan Bisnis, 2022)
The pandemic of Covid-19 influences the behaviour of worship places in doing their accountability. Indeed, it is difficult to trace the truth of the source and amount of the donated funds. The study's objective is to explore the accountability mechanisms of places of worship by exploring them in the context before and during the COVID-19 pandemic. The study is also to explore the religiosity and humanistic side of financial managers in running their duties at the mosque. This research is qualitative research using a phenomenological approach with semi-structured interview methods. This study found that accountability before and during the pandemic has a similar practice in terms of financial accountability. Interestingly, an increasing source of funds was found during the pandemic. There is additional shopping for Wi-Fi to support the mosques’ activities. The accountability of mosque financial management consists of religious (self-connection with God) and humanism (honest, trusting and responsible). Keywords : accountability, covid-19 pandemic, mosque, religiosity, humanist